The Combined Effect of Cigarette Smoking and Fitness on Injury Risk in Men and Women. Issue 12 (24th July 2018) - Brooks, Raina D; Grier, Tyson; Dada, Esther O; Jones, Bruce H
Abstract: Background: Prior studies have identified cigarette smoking and low fitness as independent risk factors for injury; however, no studies have evaluated the combined effect of cigarette smoking and fitness on injury risk. Objective: To evaluate the combined effect of cigarette smoking and fitness on injury risk in men and women. Design: This is a secondary analysis of data collected from US Army recruits ( n = 2000) during basic combat training within the United States in 2007. Physical training and fitness, cigarette smoking, and prior injury data were obtained from questionnaires, whereas demographic and injury data were obtained from medical and basic combat training unit records. Chi-squared tests were used to assess differences in injury risk by fitness level and cigarette smoking. Relative risk values were calculated with 95% confidence intervals. Results: The primary findings showed that smokers experienced 20%–30% higher risk of injury than nonsmokers. In addition, higher aerobic and muscular fitness was generally not protective against injury between least fit and more fit smokers. However, higher fitness was protective against injury between least and more fit nonsmokers, with least fit nonsmokers being 30%–50% more likely to experience an injury than fit nonsmokers. Conclusion: This study revealed that higher aerobic and muscular fitness was not protective against injury among smokers; however, it was protective against injury among nonsmokers. Further implementation of smoking cessation programs may be beneficial for military and civilian personnel who are required to be physically fit in order to carry out their job responsibilities. Implications: Male and female smokers experienced significantly higher risk of injury than nonsmokers. Although higher fitness is protective against injury in nonsmokers, the protective effect of fitness is lost among smokers. In an attempt to reduce injury risk among military and emergency personnel, smoking cessation programs should be further implemented among both more fit and less fit smokers.